Effects of two Bacillus velezensis strains isolated from different sources on the growth of Capsicum annum - Wang, Bao; Tan, Shimeng; Wu, Mingde; Feng, Yujie; Yan, Wanrong; Yun, Qian; Ji, Xuncong; Lin, Runmao; Zhao, Zhixiang (Frontiers in Microbiology, 2024)
Microbial inoculants offer an environmentally friendly approach to enhance plant growth and control disease. In this study, two Bacillus velezensis strains, HKSSLJEBR3 (R3) and Ya-1 were isolated from pepper plant roots and tropical rainforest soil, respectively. Both strains exhibited strong antifungal activity against Fusarium oxysporum f. sp. capsici, with inhibition rates of 48.54 ± 0.66% for R3 and 49.35 ± 1.44% for Ya-1. In greenhouse trials, R3 significantly boosted pepper growth, with a 22.12% increase in plant height, 46.44% more leaves, and 56.29% greater fresh weight. These enhancements were likely due to the strong affinity between R3 and pepper plants. Both strains also improved soil quality, with R3 increasing available potassium (AK) by 5.13% and soil organic matter (SOM) by 4.03%, while Ya-1 showed more significant increases. Metagenomic analysis revealed that both strains altered the rhizosphere microbiome, with R3 promoting Pseudomonas and suppressing Fusarium. These results suggest that the R3 strain has strong potential for enhancing pepper growth, improving soil health, and reshaping the rhizosphere microbiome.